EDUKASI PASAR MODAL DI MADRASAH ALIYAH MUHAMMADIYAH PEKANBARU - Siti Hanifa Sandri; Siti Samsiah; Bakaruddin Bakaruddin (Jurnal Pengabdian UntukMu NegeRI, 2018)
The capital market is a market (place, in the form of a building) prepared to trade stocks, bonds, and other types of securities using the services of stockbrokers. To add to the opening insights on the introduction of capital markets in Indonesia, the introduction of trading mechanisms on stocks and the steps to become investors in the capital market addressed to school teachers and students by practitioners who have been directly involved in the capital market in order to support the interests, knowledge and improving soft skill of teachers and students especially related to how to invest in capital market. This method of community service activities using lecture methods, direct demonstrations practiced by participants, and question and answer. Evaluation of activities generally works well and satisfies participants and training instructors. Participants hope that in the following years can be given the opportunity to get similar training. Overall activities of community empowerment through education of capital market run well and smoothly. This training provides skills and knowledge about capital market activities to teachers and learners as a provision to start a flexible and controllable side business.